Controlling a Wind Instrument with the Help of PROFINET Industrial Protocol - Liptai, Tibor; Tóth, János; Husi, Géza (International Journal of Engineering and Management Sciences, 2016)
Nowadays, the industrial communication networks are the one of the most important research area in advance control systems. It is necessary to think about controlling tasks at system level instead of local solutions. There are different types of protocols developed for communication between industrial controlling devices.